Pengaruh Massa Adsorben Pada Biosorpsi Ion Logam Cr(VI) Menggunakan Biosorben Selulosa Dari Kulit Durian (Durio zibethinus L.) - Roza Herlina; Edi Nasra; Rahadian Zainul; Trisna Kumala Sari (Periodic, 2023)
The metal ion Cr(VI) is a very toxic substance with high solubility so that it can cause pollution to the environment. If the concentration of metal ions Cr(VI) exceeds the limit of 0.5 mg/L can damage ecosystems, the environment, poison living organisms and humans, then a method is needed to overcome the pollution caused by chromium waste. Biosorption is an effective and efficient method. The purpose of this study was to determine the optimum conditions for the absorption and absorption capacity of Cr(VI) metal ions. metal ion Cr(VI) with dihenylcarbazide and H2SO4 will form a purple complex reaction. The maximum wavelength of Cr(VI) ion absorption was obtained at 543 nm. These results obtained optimum absorption conditions at an adsorbent mass of 0.6 grams with an absorption capacity of 12.7506 mg/g.